A 3D physical model to study the behavior of vegetation fires at laboratory scale. (October 2018) - Morvan, Dominique; Accary, Gilbert; Meradji, Sofiane; Frangieh, Nicolas; Bessonov, Oleg
Abstract: A 3D multi-physical model referred to as "FireStar3D" has been developed in order to predict the behavior of wildfires at a local scale (<500 m). In the continuity of a previous work limited to 2D configurations, this model consists of solving the conservation equations of the coupled system composed of the vegetation and the surrounding gaseous medium. In particular, the model is able to account explicitly for all the mechanisms of degradation of the vegetation (by drying, pyrolysis, and heterogeneous combustion) and the various interactions between the gas mixture (ambient air + pyrolysis and combustion products) and the vegetation cover such as drag force, heat transfer by convection and radiation, and mass transfer. Compared to previous works, some new features were introduced in the modeling of the surface combustion of charcoal, the calculation of the heat transfer coefficient between the solid fuel particles and the surrounding atmosphere, and many improvements were brought to the numerical method to enable affordable 3D simulations. The partial validation of the model was based on some comparisons with experimental data collected at small scale fires carried out in the Missoula Fire Sciences Lab's wind tunnel, through various solid-fuel layers and in well controlled conditions. A relative good agreement was obtained for most of the simulations that were conducted. A parametric study of the dependence of the rate of spread on the wind speed and on the fuelbed characteristics is presented. Highlights: Numerical simulations of surface fire through an homogeneous fuel bed. Detailed physical fire model. Comparison with the experiments carried out in the wind-tunnel of the Missoula Fire Sciences Lab.